Reconhecimento de seqüências de atividades funcionais em pacientes com acidente cascular encefálico - França, Fabíola Rodrigues de (2007)
During the motor rehabilitation of patients with neurological pathologies, there are many factors that have an influence on the therapeutical process. It is possible that the demonstration using videotapes or photographs of movements that will be learned can assist the codification, classification and reorganization of the elements of the task in familiar diagrams and thus facilitate the process of motor rehabilitation. The aim of this study was to analyze the performance in the test of recognition of sequences of functional activities such as water drinking and hair combing presented partially (by photos) and completely (by video) to the patients with encephalic vascular accident . The sample was generated from 12 patients (62 ± 8 years) and 10 healthy subjects (53 ± 5 years), of both sex, divided in two groups for which 5 functional activities were presented partially and completely, in 4 sequences that varied between reached and not reached objectives and correct and incorrect movements, during 24 trials. The test t'Student was applied to verify differences in the recognition time between the groups, and to compare the performance between the tests carried through at 9:00 am and retests at 9:00 am and 4:00 pm. To compare the frequency between the types of reply, the test Qui-square was used. It was verified that the patients presented a greater recognition time and a lower number of correct answers than the healthy subjects, and had better performances in the recognition of the complete sequence than the partial one. Bigger frequency was observed in the reply that the objective and the movement were being presented correctly, however the healthy subjects had soon indicated the correct reply in the first trials. An improvement tendency was observed in the performance, when the stages of tests and retests had been carried through in the same schedule. According to the results, it is suggested that the patients with stroke can better recognize the correct movements of a functional activity when it is presented completely in video form, what can influence the choice of the therapeutical strategy during the process of motor rehabilitation